A study on the critical factors which influence habitual entrepreneurs' success in networking from the perspective of social captial theory - Li, SiQi (2012)
The aim of the research is to provide an insight on the critical factors which influence habitual entrepreneurs’ success in networking through which effective networking strategies may lead to increased business performance. The perspective of explaining the factors adopts social capital theory and social dimensions of entrepreneurs’ network. The key findings suggest that social capital is in a form of non-linear pattern that the interactions are complex. Network configuration influences effective networking among habitual entrepreneurs across developmental stages. Network resources are the variable in resource embeddness influencing entrepreneurs’ network building. Relational embeddedness is found to be of impact on personal relationships (strong ties) and business relationships (weak ties), but insignificantly influences brokerage relationships (weak ties). Trust is variable which generates impact on entrepreneurs personal relationships and business relationships building (strong ties and weak ties).